Anatomic robotic prostatectomy: current best practice. (January 2019) - Martini, Alberto; Tewari, Ashutosh Kumar
Urologic prostate surgery has changed dramatically over the past decades. Following the introduction of the robot, the surgical approach has been modified and thanks to the magnification allowed by the robot a further level of precision can be achieved. Moreover, advances in the anatomical studies have provided new evidence regarding the periprostatic anatomy. The aim of this review is to describe our approach to robot-assisted radical prostatectomy. Our holistic perspective towards patient selection, pre- and postoperative care is provided. In our center, robot-assisted radical prostatectomy is performed by means of an anterograde approach. A nonbladder-sparing dissection with a graded approach towards nerve preservation is carried out. The procedure is concluded with what we call 'total anatomical reconstruction'.